Blockchain and Directions of its Using in Logistics in the Conditions of Digital Transformation - H. N. Kostukova (Цифровая трансформация, 2020)
The purpose of the article is to show the possibilities of using blockchain in logistics. In the modern world, digital technologies are used in various fields including logistics. An important achievement of modernity is blockchain. Initially, its using was related to the field of cryptocurrencies, in particular, bitcoin. Based on analysis the article reflected the essence of the blockchain, features of its functioning, marked advantages and disadvantages. The directions of using blockchain in logistics are highlighted.